The recycling problem in a currency union - G. E. Krimpas (Levy Economics Institute of Bard College, 2010)
The recycling problem is general, and is not confined to a multicurrency setting: whenever there are surplus and deficit units-that is, everywhere-adjustment in real terms can be either upward or downward. The question is, Which? An attempt is made to formulate the problem in terms of the European Monetary Union. While the problem seems clear, the resolution is not. It is proposed to engage the issue through a detour consistent with the Maastricht rules. Inadequate as this is, it highlights the limits of technical arrangements when governments are confronted with political economy-namely, the inability to set the rules of the larger game from within a set of axiomatically predetermined rules dependent on the fact and practice of sovereignty. Even so, an attempt at persuasion through clarification of the issues-in particular, by highlighting the distinction between recycling and transfers-may be a useful preliminary. Some of the paper's evocations, notably on oligopoly, may be taken as merely heuristic.
Keywords: B2; E12; E20; 330; Keynes; economic theory; international payments; jistory of thought; competitiveness; full employment; currency union; recycling problem; banking principle